2016
DOI: 10.1128/jvi.01701-16
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant T-Cell Epitopes in the VP1 Capsid Protein of Rhinovirus Species A and C

Abstract: Rhinovirus (RV) species A and C are the most frequent cause of respiratory viral illness worldwide, and RV-C has been linked to more severe exacerbations of asthma in young children. Little is known about the immune responses to the different RV species, although studies comparing IgG1 antibody titers found impaired antibody responses to RV-C. Therefore, the aim of this study was to assess whether T-cell immunity to RV-C is similarly impaired. We measured T-cell proliferation to overlapping synthetic peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…Immunodominant peptides of the VP1 capsid protein of rhinoviruses A and C, recently identified as specific for and representative of each RV‐A and RV‐C species by an epitope‐mapping study , were combined into pools representing each species (Table ). From a measure that considered the size of the stimulations of individual subjects and the frequency of stimulation in the sample (reactivity score) these peptides accounted for almost 50% of the reactivity score achieved with all the peptides for both RV‐A and RV‐C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodominant peptides of the VP1 capsid protein of rhinoviruses A and C, recently identified as specific for and representative of each RV‐A and RV‐C species by an epitope‐mapping study , were combined into pools representing each species (Table ). From a measure that considered the size of the stimulations of individual subjects and the frequency of stimulation in the sample (reactivity score) these peptides accounted for almost 50% of the reactivity score achieved with all the peptides for both RV‐A and RV‐C.…”
Section: Methodsmentioning
confidence: 99%
“…The current study describes T‐cell responses to RV‐A and RV‐C in a pediatric clinical cohort of asthma‐diagnosed children. The responses measured are induced by pools of peptides containing epitopes of the RV‐A and RV‐C VP1 proteins that are both species‐specific and representative of memory T‐cell responses made to each species . We aimed to characterize and compare T‐cell responses between RV‐A and RV‐C and to test the hypothesis that T‐cell responses would differ between asthmatic children and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on donor blood, human CD4 + T-cell epitopes were identified in VP1 capsid protein of group A and group C rhinoviruses. Interestingly, the location of the immunodominant T-cell epitopes was different for group A and group C RVs [3]. Immunodominant areas for VP1 of group A rhinoviruses were homologous with group B RVs and other enteroviruses, but not with group C RVs.…”
mentioning
confidence: 96%
“…About 90% of the serotyped RV strains use intercellular adhesion molecule-1 (ICAM-1) (so-called 'major group' of RVs), whereas strains belonging to the 'minor group' use a low-density lipoprotein receptor [2]. In addition, a cadherin-related family member 3 molecule (CDHR3) has been identified as a receptor for the RV-C group [3]. In the 1960s and 1970s, several studies of whole-virion formalin-inactivated RV vaccines administered to humans found that strong, longlasting, strain-specific protective immunity was established.…”
mentioning
confidence: 99%
See 1 more Smart Citation